The meanings of the products on the basis of the company - París, José A. (Revista Universidad de Guayaquil, 2011)
The mechanistic model of the economy brought about a paradigm of marketing, from the purely pragmatic approach and actually being based on the 4P’s drive of the quantitative research based on the market that seemed to give the basis for a marketing plan sure to succeed. This methodology showed its shortcomings and led companies to total failure. The reason: companies do not know what your customers actually buy, or worse, do not know what they sell. We affirm that, because companies do not yet have marketing methods to determine the meanings of its products. From our essential marketing paradigm, we try to go to the essence of the problem, which must surely be to detect and interpret the meanings of the products in the consumer’s mind. From this approach we have developed heuristic techniques outcrop of meanings. To access them you must work with homogeneous groups and define market segmentation process into three stages: pre-segmentation, segmentation ad hoc and final segmentation.